Allocation of Working Time and Contribution of Independent Oil Palm Farmers' Income to Household Economy in Musi Rawas Regency - Lifianthi Lifianthi; Serly Novita Sari; Andy Mulyana (Journal of Global Sustainable Agriculture, 2026)
Utilization of work time allocation is one of the important factors in increasing work productivity to improve the economic capacity of independent oil palm farmers' households. This study aims to allocate work time between oil palm farming, off-farm and non-farm activities, the contribution of oil palm farming income to total household income to calculate the level of economic capacity of independent oil palm farmers and the distribution of total income distribution of independent oil palm farmers' households. The method used is the census method conducted in STL Ulu Terawas District and Sukakarya District, Musirawas Regency, South Sumatra. The location was chosen because these two locations are independent oil palm producers, each location was taken by 50 independent oil palm farmers with a total of 100 respondent farmers. The data collected were primary data through structured interviews and questionnaires, while secondary data were obtained from related agencies. The results of the study show that the allocation of working time carried out by family labor is 97.56 HOK/year for oil palm farming, 198.24 HOK/year for non-oil palm farming, and 167.48 HOK/year for non-farming. The potential working time of the respondent's farmer family is 613.14 HOK/year with the family's free time being 149.86 HOK/year. These results prove that the respondent's farmer family, in addition to being able to carry out three activities, still has free time allocated to carry out other productive activities and social activities. Income from oil palm farming activities is Rp37,431,611, - with a contribution of 55.52% to the total income of respondent farmers, this shows that independent oil palm farming dominates the source of income for farmer families. The distribution of income distribution of respondent farmers from low and high incomes, obtained a Gini index value of 0.489